KDIGO 2020 Clinical Practice Guideline for Diabetes Management in Chronic Kidney Disease: Summary of recommendation statements and practice points translated into Ukrainian - Dudar, I.; Loboda, O.; Savchuk, V. (Ukrainian Journal of Nephrology and Dialysis, 2020)
The paper presents the summary of recommendation statements of the "KDIGO 2020 clinical practice guideline for diabetes management in chronic kidney disease" translated into Ukrainian.